2022
DOI: 10.3390/healthcare11010084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transcranial Direct Current Stimulation and Exercise on Fatigue and Quality of Life in Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system that leads to a great deterioration in the quality of life. Objective: We aimed to assess the effectiveness of two individual programs, one based on transcranial direct current stimulation (tDCS) and another based on the effect of physical exercise on fatigue and quality of life in patients with MS. Methods: A total of 12 patients with relapsing–remitting and progressive secondary MS participated. Fatigue and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The included studies used a variety of study designs to detect, quantify and examine MS-related fatigue. The 19 articles, shown in Table 1, employed the following study designs: 5 studies case–control studies (Buyukturkoglu et al, 2017; Conte et al, 2016; Gscwind et al, 2016; Russo et al, 2017; Vecchio et al, 2017), 3 cross-sectional studies (Chaves et al, 2019; Newland et al, 2021; Paolicelli et al, 2021), one prospective-observational study (Chalah et al, 2019); one correlational (Russo et al, 2017); one single blind, within-subject design (Fiene et al, 2018), and one cross-over study (Muñoz-Paredes et al, 2022). Seven of the 19 studies utilized a double-blind RCT study design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies used a variety of study designs to detect, quantify and examine MS-related fatigue. The 19 articles, shown in Table 1, employed the following study designs: 5 studies case–control studies (Buyukturkoglu et al, 2017; Conte et al, 2016; Gscwind et al, 2016; Russo et al, 2017; Vecchio et al, 2017), 3 cross-sectional studies (Chaves et al, 2019; Newland et al, 2021; Paolicelli et al, 2021), one prospective-observational study (Chalah et al, 2019); one correlational (Russo et al, 2017); one single blind, within-subject design (Fiene et al, 2018), and one cross-over study (Muñoz-Paredes et al, 2022). Seven of the 19 studies utilized a double-blind RCT study design.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (Cancelli et al, 2018;Chalah et al, 2017Chalah et al, , 2020Charvet et al, 2018;Hanken et al, 2016;Mortezanejad et al, 2020;Muñoz-Paredes et al, 2022) tested the effect of tDCS on cognitive fatigue. Among these 7 studies, 6 used a cross-over design and only one was an RCT (Muñoz-Paredes et al, 2022). Investigators in all 7 studies reported fatigue was significantly improved after tDCS.…”
Section: Tdcs Studiesmentioning
confidence: 99%
See 3 more Smart Citations